Continuous quantum phase transitions in the one-dimensional spin-1/2 axial next-nearest-neighbour Ising model in two orthogonal magnetic ¯elds - ADEGOKE, KUNLE; BÄUTTNER, HELMUT (Indian Academy of Sciences, 2020)
PRAMANA journal of physics, VOL. 74, No. 2, P. 293-306